ALTERNATIVE PARADIGM TO COMMUNITY DEVELOPMENT: THE INFLUENCE OF COMMUNITY BASED ORGANISATION ON COMMUNITY DEVELOPMENT IN OYO STATE, NIGERIA - Lawal Ayofe BAKARE; Victoria Olubukola OGUNYEMI (International Studies Journal)
This study investigated the influence of Community Based Organisation on community development in the selected local government areas of Oyo State, Nigeria. The study adopted survey research design and utilized primary data obtained through the administration of questionnaires. A total of four hundred and twenty (420) members were randomly selected for the study from the two LGAs for the purpose of this study at Two Hundred and Ten (210) members per LGA, including the CDC executive members. Both the descriptive and inferential analysis was carried out on the data obtained with the aid of SPSS package. The study revealed that the nature of CBOs operation in the selected local governments can be seen in the construction of drainage facility; provision of electric poles; construction of town hall; Provision of borehole/pipe-borne water or community well; provision of blocks of classrooms for school(s) in the community; provision of furniture/equipment for the school and other key aspects of social and economic development. It was equally revealed that the people expressed high satisfaction with CBOs projects in the following areas; provision of electric poles, provision of transformer(s), provision of borehole/pipe-borne water or community well, construction of town hall and construction of drainage facility. However, they have low satisfaction in the area of rehabilitation of and/or construction of primary healthcare facility, provision of blocks of classrooms for school(s) in the community, and provision of furniture/equipment for the school. It was also established that the constraints to effective execution of projects by CBOs in the study area include mismanagement of funds by community project management committee, inadequate funds to execute projects, uncooperative attitude of project management committee members, uncooperative attitude of members of the community towards their contribution for community project, It was concluded from the study that Community Based Organisations has strong and significant influence and contribution on/to community development in the selected local government areas of Oyo State, Nigeria. Hence, it was recommended that government, NGOs and development agencies should recognise and reinforce the positions of CBOs in the rural development process.